RELASI TANDA DAN NILAI FILOSOFIS PIRANTI TRADISI ENTAS-ENTAS SUKU TENGGER: KAJIAN ANTROPOLINGUISTIK - Putri, Vranola Ekanis; Abidin, Muhammad Irvanul; Hasyim, Ali; Thalares, Titania Dena; Nathasia, Hana; Luhur, Gagawan Jawa Anjawani; Ardhian, Dany (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2022)
The Tenggerese are still thick with their culture, especially at death ceremonies. Of course, inthe tradition of the Day of Death, the Tengger tribe has its own uniqueness and sacrednessthat makes it interesting. The purpose of this study is to explain the lingual form, meaning,referential, and philosophical values of the Tenggerese Death Day tradition in Anthropologystudies.The Tenggerese are still thick with their culture, especially at death ceremonies. TheDay of the Dead tradition begins on the day of death until someone's funeral. Of course, in thetradition of the Day of Death, the Tengger tribe has its own uniqueness and sacredness thatmakes it interesting. The purpose of this study is to explain the lingual form, meaning,referential, and philosophical values of the Tenggerese Death Day tradition in Anthropologystudies.The source of the data in this study was obtained from documentation and interviewswith traditional leaders of the Tengger tribe, Romo Eko and Romo Pram. From these sources,it can be found tools used in day of death rituals such as nyigar ontong, isen-isen, treats andothers. The data collection method that will be used is the listening and note-taking technique.The data analysis method will use the discourse analysis method. Discourse analysis waschosen to study the use of written or written language in relation to social contexts. Then thereferential meaning used is based on the triangle of meaning of Ogden and Richards with thecategories of culture, social, history, nature, religion, and economy. The results of the studyfound that the lingual form obtained from the death ceremony was in 2 categories, namelyaffixation and reduplication, while the referential meaning found 15 meanings. Thephilosophical values in the Tengger death tradition include moral philosophy and also thephilosophical values of adat/tradition